N. F. S. Grundtvig: Rim-Brev til Nordiske Paarørende, 1832. Tekstkritisk og kommenteret udgave - Lundgreen-Nielsen, Flemming (Grundtvig-Studier, 2008)
N. F. S. Grundtvig: “Rim-Brev til Nordiske Paarørende”, 1832. Tekstkritisk og kommenteret udgave [N. F. S. Grundtvig: Rhymed Epistle to the Norse Kinsmen ”, 1832. Critical and annotated edition] By Flemming Lundgreen-Nielsen Grundtvig’s “Rhymed Epistle to the Norse Kinsmen” (258 verses), published as a prologue to Norse Mythology or The Language of Myth, 1832, is reprinted in a densely annotated version, with attention being given to manuscripts in the Grundtvig Archive and statements in Grundtvig’s other writings as well as to earlier scholarly treatments. Emphasis is placed on the extent to which Grundtvig employs ambiguous imagery with a multitude of mythological details which may be categorised according as they derive from medieval sources such as The Prose Edda of Snorri Sturluson, poems of The Elder Edda and The Danish Chronicle by Saxo. In a Postscript, the text as a whole is located in Grundtvig’s secular writings in exactly that period when he coins the phrase “First a Man, then a Christian”, thus heralding a humanistic approach to an education for citizenship and practical everyday life. It is among numerous other things demonstrated that the still frequently quoted lines about freedom for Loki as well as for Thor and about struggle and competition historically viewed embody meanings different from those routinely assumed by modem users.